2020
DOI: 10.26434/chemrxiv.12454100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceleration of Lipid Reproduction by Emergence of Microscopic Motion

Abstract: <p>Self-reproducing chemical systems are essential for organic matter to reproduce, move and grow. In artificial settings, chemical reactions can show rich dynamics and auto-catalytic characteristics, however achieving higher order functionality from self-reproducing chemical systems remains a current challenge. Here, we show that <a></a><a>self-reproducing lipids can initiate, sustain and accelerate the movement of microscopic oil droplets in water and, in return, the chemotactic movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In a solution of trans-Azo, the droplets move in all directions autonomously (Figure 2A), provided that the concentration of the Azo amphiphile is above a concentration that we call critical propulsion concentration 37 (CPCtrans = 0.8 mM), which is typically higher than the critical micellar concentration (CMCtrans = 0.5 mM). We found that increasing the concentration of trans-Azo amphiphile leads to an increase in the average speed of the oil droplets because the concentration of micelles that fuel motility increases with the concentration of switch (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…In a solution of trans-Azo, the droplets move in all directions autonomously (Figure 2A), provided that the concentration of the Azo amphiphile is above a concentration that we call critical propulsion concentration 37 (CPCtrans = 0.8 mM), which is typically higher than the critical micellar concentration (CMCtrans = 0.5 mM). We found that increasing the concentration of trans-Azo amphiphile leads to an increase in the average speed of the oil droplets because the concentration of micelles that fuel motility increases with the concentration of switch (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%